Improving machine vision crack die detection with multi-kernel learning SVM - Abdullah, Mohd Khairi John (2024)
With the rising need to produce semiconductor parts with zero defects to support the growth of the automotive industry, where safety must be assured, it is vital to perform visual inspection throughout the assembly process to isolate and detect defects. Visual inspections performed by a human have two generic issues. Firstly, the variation in the measurement taken due to variations in readings taken by different individuals would impact the decision to separate and remove the defective products. Secondly, the inaccurate measurement of the size and decision makes it difficult to analyse.